COMPARISON OF TWO 8-WEEK TRAINING INTERVENTIONS ON THE ATHLETIC PERFORMANCE OF PADEL PLAYERS (Kinesiology, 2023)
Padel is an intermittent racket sport played in pairs (2 vs. 2) on a small-sized grass court (20 x 10 m), involving high physical fitness demands for the players. Therefore, this study aims to compare the effect of two 8-week in-season training programs on the athletic performance of male padel players. Participants (age, 22.1±0.8 yr; body height, 182.0±1.0 cm ; body mass, 74.7±0.7 kg) were randomly assigned to the integrated training group (IG, n=12) and non-integrated training group (NIG, n=12). The IG trained inside the padel court, integrating neuromuscular exercises with sport-specific (i.e., use of the racket) technical actions. The NIG trained outside the padel court, performing the same neuromuscular exercises and sport-specific technical actions as the IG, although not simultaneously. Before and after the intervention, athletes were assessed for their hand-grip strength, two legged and one-legged Abalakov jump, bench press performance, padel stroke velocity, cardiorespiratory endurance (30-15IFT), 5-m and 10-m linear sprint time and change of direction ability at 90º and 180º using left and right leg. Both groups improved their scores on Abalakov jump tests, bench press performance, stroke velocity, cardiorespiratory endurance (30-15IFT), and change of direction ability at 90º and 180º (all changes p